Tackling the complexity of obesity in the US through adaptation of public health strategies - Ard, Jamy; Huett-Garcia, Amber; Bildner, Michele (Frontiers in Public Health, 2025)
Obesity prevalence continues to rise in the US despite more than two decades of recommendations and guidelines for its prevention and management. The encouragement of individuals to adopt a healthy diet and lifestyle has remained the focus of clinical interventions and recommendations despite these efforts alone proving ineffective for long-term weight management. There are many recognized barriers to obesity prevention and management in community and clinical settings including political factors, social determinants of health, weight bias and stigma, and inequities in access to treatment and insurance coverage. We discuss these barriers in more detail and attempt to identify areas where public health and healthcare approaches can be better aligned, allowing for better advocating by public health officials to enable a more meaningful and population-level change in obesity prevention and management in the US.